El modelo del sistema viable: una referencia estratégica para el estudio organizacional del sector cooperativo chileno - Narvarte Arregui, Pedro Antonio; Careaga Díaz, Catalina (REVESCO. Revista de Estudios Cooperativos, 2015)
The Chilean Cooperative Sector (SCCh) can be explained as a human activity system of high complexity, which seeks to maintain an independent existence, in example, be viable. From this perspective, the Viable System Model (MSV) as conceptual reference presents a real opportunity to study the organization of the cooperative sector in Chile. The central objective of the work refers to study the feasibility of SCCh in a context of sectorial organization, considering the social, legal and economic fabric of the country today. To do this, supported by a systemic methodology were performed: a characterization of the problem situation of the sector -identifying some relevant factors in the areas of market structure, legal regulations and inter cooperation-an organizational diagnosis and proposed a set guidelines for its development. From the above it is concluded that there is relevance between the characteristics of the case study theoretical and methodological approach. The methodology takes tested in other organizational practices such as VIPLAN tools, and applies the SCCh. Its contribution in the field of study is oriented around a holistic view of the organization and promotion of their viability, thereby generating an approach that delivers specific sectorial development strategies, surpassing the approximation of descriptive characterization. Thus, we provide a diagnostic model of the Chilean Cooperative Sector and propose guidelines to support their organizational development.